INVESTMENT ACTIVITY: ESSENCE, THE ESTIMATION AND THE IMPACT ANALYSIS ON SOCIOECONOMIC DEVELOPING OF REGION - L. N. Salimov (Russian Journal of Economics and Law)
The results of regional investment activity research are presented in the article. The urgency of a theme is stipulated by necessity of auditing and clarification of some theoretical provisions concerning influence of investments on socioeconomic development of regions in new conditions - in conditions of becoming a postindustrial economy and amplification of international economic integration. Regional investment activity, in author's opinion, is the interrelation and dynamics of the size and structure of investments in economy of region, their sources and results. The author advances techniques of estimations of regional investment activity and of impact analysis of investment activity on socioeconomic development of region.